DEVELOPMENT OF THE CHURCH HURIA KRISTEN BATAK PROTESTAN RESSORT PALEMBANG 2010-2020: Perkembangan Gereja Huria Kristen Batak Protestan Ressort Palembang Tahun 2010-2020 - Itasari Simbolon; Farida R. Wargadalam (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Abtract This study examines the development of the Huria Kristen Batak Protestan (HKBP) Church in Palembang from 2010 to 2020, focusing on its growth in congregation size, improvements in church facilities, and adaptation to social and technological changes. The research addresses the challenges faced by the church, such as shifting worship methods during the COVID-19 pandemic, and explores the factors contributing to its sustained development and community impact. Employing a historical research method, the study systematically collected and analyzed primary and secondary sources, including interviews with church leaders, archival documents, and field observations. It integrated sociological and anthropological approaches to deepen understanding of the church’s social dynamics and cultural significance within the Batak community in Palembang. The HKBP Palembang church demonstrated significant growth, with congregation numbers increasing from 1,112 in 2010 to 3,473 in 2020. The church expanded its infrastructure, enhanced social services, and adopted digital worship platforms during the pandemic, maintaining spiritual connection despite physical restrictions. Leadership development through the Preparation Training Program ensured quality pastoral care. These developments underscored the church’s role as a vital religious and social hub for the Batak community. While the study provides a comprehensive overview of HKBP Palembang’s evolution, its historical and qualitative nature limits generalizability to other contexts. Constraints included reliance on available documents and interviews, which may reflect subjective perspectives. Future research could broaden focus to comparative studies across other HKBP branches or explore the impact of digital ministry on congregation engagement more deeply.